Biologia de Meloidogyne exigua: I. Desenvolvimento embriogênico e efeito da temperatura na embiogênese - D’Arc de Lima, Rosângela; Ferraz, Silamar (Revista Ceres, 2025)
The embryogenesis of Meloidogyne exigua was studied under different temperature regimes.